Pengaruh Media Edukasi Audiovisual Terhadap Kesiapsiagaan 5M Memutus Penularan Covid-19 Pada Karang Taruna Asta Dharma - Ni Putu Anggi Widyasari; I Ketut Sudiantara; I Ketut Gama; Agus Sri Lestari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
The number of Covid-19 cases continues to increase until January 2021. It is necessary to increase 5M preparedness to stop the transmission of Covid-19. Several studies have revealed that health education with audiovisual educational media is effective for increasing community preparedness during the Covid-19 pandemicThe aims of researchtodetermine the effect of audiovisual education on 5M preparedness to break transmission Covid-19 on Karang Taruna Asta Dharma. This type of research is a quantitative pre-experimental design with one group pre-post design using simple random sampling with 40 respondents. The results showed that the preparedness before being given educational media was in the preparedness 65-79 (ready), are 31 respondents (77.5%). Preparedness after being given educational media 80-100 (very ready) are 37 (92.5%). The results of the Wilcoxon statistical test were p value = 0.000 less than alpha (0.05) which means that Ho was rejected, it was concluded that there was an effect audiovisual education against preparedness 5M break transmission Covid-19 at Karang Taruna Asta Dharma, Sanur Kaja Village, 2021.